2017
DOI: 10.1002/oby.21807
|View full text |Cite
|
Sign up to set email alerts
|

Ability to adjust nocturnal fat oxidation in response to overfeeding predicts 5‐year weight gain in adults

Abstract: ObjectiveTo determine whether metabolic responses to short-term overfeeding predict longitudinal changes in body weight.Methods24h energy expenditure (EE) and substrate utilization were measured at baseline in a room calorimeter following 3d of eucaloric and hypercaloric feeding (40% excess) in a sample of lean adults (n: 34; age: 28±2 years; body mass index: 22±3 kg/m2). Body mass and fat mass (DXA) were measured annually for 5yrs. Regression analyses examined whether changes in EE and fuel use with overfeedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…One feature that appears to distinguish OP and OR adults during periods of OF is the ability to maintain total fat oxidation at levels similar to energy‐balanced conditions, particularly at night . In the EATS, we showed that OF of a mixed diet led to an overall increase in daytime carbohydrate oxidation at the expense of fat oxidation in both OP and OR groups .…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…One feature that appears to distinguish OP and OR adults during periods of OF is the ability to maintain total fat oxidation at levels similar to energy‐balanced conditions, particularly at night . In the EATS, we showed that OF of a mixed diet led to an overall increase in daytime carbohydrate oxidation at the expense of fat oxidation in both OP and OR groups .…”
Section: Discussionmentioning
confidence: 72%
“…We found that OR participants maintained whole‐body fat oxidation rates at night during sleep during OF, whereas nocturnal fat oxidation decreased in OP participants . Surprisingly, individual differences in nocturnal fat oxidation responses to OF correlated with longitudinal weight gain .…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Our previous investigations have primarily focused on identifying differences between OP and OR in fuel utilization and EE during a period of imposed OF. We found that both those with OP and those with OR exhibit similar responses in 24‐hour EE and macronutrient oxidation; however, those with OP tend to downregulate nocturnal fat oxidation, which may drive weight gain . In a separate set of experiments, those with OP reported higher hunger, restraint, and disinhibition compared with those with OR .…”
Section: Introductionmentioning
confidence: 65%
“…Excess ingested fats that are not oxidized are stored in the body as adipose tissue ( 67 ), ultimately leading to weight gain. In a recent study, reduced fat oxidation during sleep following 140% overfeeding a balanced diet for three days predicted greater free-living weight gain after five years ( 3 ). Similarly, a failure to increase fat oxidation during one day of 200% overfeeding a diet with 60% calories from fats also predicted weight gain over the period of a year (manuscript in preparation)( 69 ), indicating that impaired metabolic flexibility (or inflexibility) in the context of a high-fat overfeeding diet is a metabolic predictor of weight gain.…”
Section: Introductionmentioning
confidence: 99%